Removal of antimony from water using GEH sorption material at different filter bed volumes - Barloková, Danka; Ilavský, Ján; Munka, Karol (International Conference “Environmental Engineering”, 2017)
The article presents the results of antimony removal from the water at Dúbrava water resource using GEH sorption material at three different amounts (volumes) of the filter bed. Based on the results of the experiment we calculated the linear dependences of the amount (volume) of the bed and the absorption capacity, the time of contact of water with the material, bed volume (V/V0 ratio), the duration of filtration and the adsorbed antimony volume in the filter bed. These values were deter mined for antimony concentrations of 5 g/L at the outlet from the filter columns, i.e. for limit concentrations of antimony in drinking water, with an average concentration of antimony in raw water being 90.3 g/L and the average filtration rate being in the range from 5.3 to 5.4 m/h.
Keywords: drinking water; filtration; iron-based sorption materials; removal of antimony; medium height